Peripheral giant cell granuloma: a case repo - Ahmed, Saad Shahnawaz; Zaman, Hira; Bin Abrar, Fahad; Khalid, Sadia (Journal of Oral and Dental Sciences, 2016)
Peripheral giant cell granuloma (PGCG) is a common benign gingival lesion in the oral cavity of unknown origin, believed to be stimulated by local irritation or chronic trauma. It is also known as giant cell epulis, giant cell reparative granuloma, or giant-cell hyperplasia, presenting as purplish-red soft tissue nodule clinically and histologically consisting of multinucleated giant cells in a background of mononuclear stromal cells and extravasated red blood cells. This case report describes a 40 year old male previously reported with peripheral giant cell granuloma 2 years back which on excision reoccurred after 3-4 months and persistently growing since then. The gingival lesion between his maxillary central incisors was excised and the Biopsy specimen sent in 10% formalin to histopathological lab and was diagnosed as PGCG. There was good healing of tissue of the surgical site during the 9 months follow-up.
Keywords: Anesthesia; Excisional Biopsy; Giant Cell; Granuloma; Lesion